2010
DOI: 10.1126/science.1183226
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Induced Hole Doping in Wide–Band-Gap Uniaxial Semiconductor Heterostructures

Abstract: Impurity-based p-type doping in wide-band-gap semiconductors is inefficient at room temperature for applications such as lasers because the positive-charge carriers (holes) have a large thermal activation energy. We demonstrate high-efficiency p-type doping by ionizing acceptor dopants using the built-in electronic polarization in bulk uniaxial semiconductor crystals. Because the mobile hole gases are field-ionized, they are robust to thermal freezeout effects and lead to major improvements in p-type electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
521
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(538 citation statements)
references
References 20 publications
16
521
0
1
Order By: Relevance
“…Non-conventional doping schemes such as 3D superlattice doping and polarizationassisted doping can potentially be used to significantly increase the p-doping concentration in high-Al-content Al x Ga 1−x N layers. [267] The issue of light extraction and hole transport might also be addressable through the use of interband tunnel junctions. [206] New device designs and material deposition approaches to manage the strain and polarization in UWBG heterostructures are also being explored with some initial success.…”
Section: Algan Materials Physics and Device Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-conventional doping schemes such as 3D superlattice doping and polarizationassisted doping can potentially be used to significantly increase the p-doping concentration in high-Al-content Al x Ga 1−x N layers. [267] The issue of light extraction and hole transport might also be addressable through the use of interband tunnel junctions. [206] New device designs and material deposition approaches to manage the strain and polarization in UWBG heterostructures are also being explored with some initial success.…”
Section: Algan Materials Physics and Device Challengesmentioning
confidence: 99%
“…The projection uses the experimentally derived E C for GaN [59] as the baseline (corrected for the updated values of mobility and permittivity in the table), as this is the highest known E C for any GaN or SiC diode. These projections follow the method described in detail in Hollis and Kaplar, [60] and, to ensure a level playing field for all materials, [29,54] n (Si) below 80-85% Al; p (Mg deep) [54,97] ; polarization doping [355,356] Possible S donor [97] ; no good acceptor Polarization-induced 2DEG n type (Sn, Si, Ge donors) [357] ; no known acceptor n type (S donor); deep acceptors [98] Light to medium p type for N A < mid- [106,107] 2018: 38 mm. [105] 2018: 38 mm.…”
Section: Materials/device Properties (mentioning
confidence: 99%
“…However, recent reports have shown that by exploiting the strong internal piezoelectric fields present in nitride heterostructures, it is possible to reduce the depletion width of the p-n junction and achieve the strong tunneling of carriers through such a structure. 22,23) For example, by inserting an InGaN well into the p-n junction region, it is possible to reduce the specific resistance of the junction to 10 −4 Ω·cm. 2,4) It was also demonstrated that by introducing GdN nanoislands, the tunneling through the midgap states inside the TJ was enhanced.…”
mentioning
confidence: 99%
“…Moreover, In the recent years, the topic of growing N-polar GaN with comparable high crystal quality to Ga-polar GaN has attracted much attention [98][99][100], due to the special advantages of N-polar thin films over Ga-polar ones [43,[101][102][103][104]. Mg, In and Si are used to assist to get rid of the disadvantages of the N-polar film growth on traditional sapphire and SiC substrates [99,105].…”
Section: Table IImentioning
confidence: 99%